(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The current paper investigates the accompanying issues like, The requirement for supply chain management, Type of supply chain management model(s), Framework of the supply chain management model Though, the SCM have found the versatility of applications, more so in the private sector enterprises (business environment) for cost cutting and for having a competitive advantage. In the government set-up though the basic objective, is not maximization of profit, but the social-economic development of people. Thus, the SCM has many applications in the government environment too. The paper highlights some of the typical applications in the government sector of the SCM paradigm.